Mini Implant as The Anchorage in Skeletal Malocclusion Class II (Case Report) - Chitra Martalia (Science and Technology Publications, Lda, 2017)
A face profile which has disharmony in skeletal maloclusion class II makes it difficult to perform the treatment conventionally with the application of a face mask and head gear. Recently, through the development of technology in dentistry, mini implants have been discovered to correct skeletal maloclusion class II and can be used for maximum anchorage. Objective: This treatment was applied to correct skeletal maloclusion class II by using a mini implant as the anchorage, thereby balancing the face profile. Case: A male patient, 23 years old, had the main complaint that his front teeth were prominent with some gaps between the teeth that caused an unpleasant appearance. The patient admitted that he had a finger sucking habit. Cephalometry showed SNA 83⁰, SNB 76⁰, ANB 7⁰, NA-APog 9⁰ (convex), AB-Npog -8⁰ (skeletal class II), Y line 62⁰ (normal), interincisal angle 102⁰ (protrusion), distance I-APog 20mm (protrusion), INA angle 42⁰(protrusion), I-NB angle 35⁰(protrusion), Wits AO-BO 6mm (class II), and Naso Labial angle 105⁰. Clinical examination showed an overjet of 12 mm, overbite of 4 mm, molar and caninus relation lass I. Case Management: The application of fixed orthodontic appliance. Anterior upper jaw leveling until Ni-Ti 0,16 x 0,16 in 4 months, the insertion of a mini implant with a diameter of 2 mm and length of 10 mm on 1/3 of the apical region of the teeth in regions 16 – 17 and 26 - 27. One week after the insertion of the mini implant, retraction of the anterior teeth was performed by the en masse technique with a power chain using an archwire SS 0,16 x 0,16. Discussion: After 4 months of the treatment using the mini implant, overjet and diastema decreased. The patient is still being treated. The next treatment is to extract four teeth: premolar 1 of the upper and lower jaw to correct the overjet.